BASIC PRINCIPLES OF THE PERSONAL-DEVELOPING EDUCATION PROCESS QUALITY - Сілакова, Т. Т. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
Based on analysis of the requirements that are currently imposed on the system of higher education society, and individuals, the authors formulated the basic principles and proposes specific measures to facilitate the implementation of personal-developing educational methodologies in the practice of higher technical education at the educational process, and at the quality control. It is shown that personality traits significantly influence student learning outcomes, and the inclusion of these qualities at all stages of the educational process as it increases the effectiveness and objectivity of the assessment of the student academic achievements in the higher education